Pengaruh Chief Financial Officer Berlatar Belakang Akuntan terhadap Audit Fee - Wulandari, Desy; Harymawan, Iman (Jurnal Riset Akuntansi dan Keuangan, 2021)
This study aims to examine the association between accountant Chief Financial Officer (CFO) and audit fee. This study also aims to examine whether accountant CFO affects audit fee when firms have high ratio of leverage, inventory and receivable, and cash. This study uses Ordinary Least Square Regression analysis model to test its hypothesis. The sample consists of 699 firm-year observations covering the period 2010 to 2017. The result shows that accountant CFO is not associated with audit fee, but when leverage is high, accountant CFO is negatively and significantly related to audit fee. This study also finds that accountant CFO doesn’t affect audit fee when inventory and receivable ratio is high, but it has significant negative effect on audit fee when firm has high ratio of cash. This study has implications as consideration in making decisions, regarding expertise and background of finance director related to audit fee when firms have high ratio of leverage and cash.